Influência da faixa etária e da manutenção da prática em parâmetros cognitivos, funcionais e antropométricos de adultos e idosos engajados em um programa exercícios físicos multicomponente: um estudo longitudinal de 5 anos - João Gabriel da Silveira Rodrigues (2023)
Human beings manifest a variety of functional losses, highlighting musculoskeletal, cardiovascular, and nervous systems impairments. Anthropometric and cognitive alterations, muscle strength, and functional capacity reductions also occur throughout aging. Physical exercise is a cornerstone of successful aging, potentially contributing to maintaining cognitive functions, body composition, functionality, and muscle strength. Furthermore, the maintenance of physical exercise practice seems necessary to preserve these promising healthy benefits of exercise in older population. This thesis compared, through two distinct studies, (1) the influence of age group on cognitive, functional, and anthropometric parameters of middle-aged adults and middle-aged and elderly adults participating in a physical activity program, (2) the progression of functional, anthropometric, cognitive and blood pressure variables in middle-aged and elderly adults after five years of follow-up. Methods: Four hundred and seventy-three older adults aged 55 to 84 years (84% women), regular participants in the Programa Envelhecimento Ativo (EEFFTO-UFMG) were enrolled in the first study. Eighty-five older women re-evaluated after five years were enrolled in the second study. The first study was conducted in 2017 and 2018, and the second in 2022 and 2023. Tests were carried out to evaluate cognitive functions (Montreal Cognitive Assessment, verbal fluency test, Digit Span test, Stroop Color, and Word test), functional capacity ("Senior Fitness Test" battery, handgrip strength, 10-meter gait test), anthropometric assessment (body mass, height, circumferences and skinfolds), and blood pressure. All procedures performed were approved by the university's Research Ethics Committee (CAAE: 49313121.0.0000.5149). Results: The older age group showed a reduction in global cognition and specific cognitive domains. In addition, there was also a reduction in muscle strength, muscle power, and functional capacity, a worsening of agility scores, and anthropometric changes (reduction in height, muscle mass, circumferences, and skinfolds). Muscle strength explained only 2.7% of the global cognition of older adults. In the second study, it was observed that maintaining the practice of multicomponent physical exercises for five years caused functional improvements and reduced the risk of cognitive decline compared to the group who abandoned the practice during the period. Conclusion: By several low-cost variables, the study showed that middle-aged and elderly adults of different age groups showed significant cognitive, functional, and anthropometric differences. Furthermore, maintaining the practice of multicomponent physical exercise can reverse at least part of the effects of aging on strength, power, and muscle mass and appears to prevent the risk of cognitive decline after five years.